SOME ASPECTS OF GEOLOGICAL STRUCTURE OF MIHAJLOVSKO-BELGOROD SUTURE ZONE OF VORONEZH CRYSTALLINE MASSIF WITHIN THE NORTHERN EDGE OF DNIEPER-DONETS-DEPRESSION - Omelchenko, V.; Pigulevskiy, P. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
This paper considers the main features of the geological structure of the Ukrainian part of the Mihajlovsko-Belgorod suture zone (MBSZ), the Voronezh Crystalline Massif (VCM) on the basis of qualitative and quantitative interpretation of the gravity and magnetic fields and by studying core samples from oil and gas wells. The MBSZ on the territory of Ukraine stretches within the northern edge of the DDD and the Dnieper graben for over 140 km with the predominant width of 3-5 km and is timed to coincide with the mantle localized deep fault of the same name dividing varied age megablocks of the VCM. On the northern edge the zone consists of three tectonic elements: south-east closing of Belgorod synclinorium, Burlutsk and Maksalsk synclines which are characterized by a tectonic joint. The MBSZ is broken into pieces (blocks) mainly by sublatitudinal faults, including shift type. The amplitude of displacement on shifts increases in a direction to Dnieper graben from 200-500 m to 10 km (?). Burlutsk syncline is a basic element of the MBSZ on the northern edge and stretches for about 55 km with a width of 2-5 km. In respect to the structure it presumably is a single-limb syncline with high dipping of layers (to 75-85о). The section of the syncline is formed by micaceous, granatum-micaceous and amphibolite slates with interlayers of ferruginous-micaceous quartzites which can be assigned to lower parts of the Kursk series of Paleoproterozoic. Geophysical and drilling data indicate the following in the development of the suture zone: Paleoproterozoic rift trough arisen out of formations of the lower parts of the Kursk series; Meso- Archean graben-like trough arisen from formations of Alexandrovsk series of the Mihajlovsk complex, and early Archean suture formed by basite-hyperbasite associations. Sharp reduction of width of the MBSZ within the northern edge from 19 km around Belgorod synclinorium to 3-5 km within Burlutsk and Maksalsk synclines, as well as absence of all Oskolsk complex and the upper part of the Kursk series in its Paleoproterozoic section is caused, mainly, by essential increase in level of an erosive cut of Pre-Cambrian formations in the direction to Dnieper graben. The stated results of the research can be used at correlation of structures of the VCM and the Ukrainian Shield through the territory of the DDD, and also for estimation of perspectives of the oil-and-gas-bearing capacity and some solid minerals of the northern edge territory.
Keywords: Mihajlovsko-Belgorod suture zone; northern edge of the DDD; geophysical anomaly; Burlutsk syncline; a Kursk series; a tectonic fault